CROSSING BORDERS sinology in translation studies. (Asian translation traditions series., 2022)
Investigates translations from the languages of China into the languages of Western societies, from the 17th to the 20th centuries. Rather than focusing solely on the activity of translation, the authors extend their explorations to cover the contexts within which the translators worked from different perspectives.